2011
DOI: 10.2147/cia.s21775
|View full text |Cite
|
Sign up to set email alerts
|

Medical treatment and long-term outcome of chronic atrial fibrillation in the aged with chest distress: a retrospective analysis versus sinus rhythm

Abstract: Although “chest distress” is the most frequent complication in the aged with chronic atrial frbrillation (AF) in clinical practice, there are few data on the association between chronic AF and coronary artery disease (CAD) in the aged in terms of medical treatment and long-term outcome. We assessed coronary artery lesions in such patients and evaluated the efficacy of medical treatment in long-term follow-ups. Of 315 elderly patients (mean age: 77.39 ± 6.33 years) who had undergone coronary angiography for che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
2
0
0
Order By: Relevance
“…Although chest pain characteristics are much more specific in evaluating patients with the chronic coronary syndrome, acute tachycardia symptoms might mimic typical angina and can be defined as disabling in up to 86% [9]. Similar to our results, a study by Guo et al that focused on the elderly population (mean age 77.4 ± 6.3 years) showed that chest distress experienced by patients with AF was not related to the prevalence of significant CAD [10]. In our study chest pain type was not associated with the prevalence of significant CAD as well.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Although chest pain characteristics are much more specific in evaluating patients with the chronic coronary syndrome, acute tachycardia symptoms might mimic typical angina and can be defined as disabling in up to 86% [9]. Similar to our results, a study by Guo et al that focused on the elderly population (mean age 77.4 ± 6.3 years) showed that chest distress experienced by patients with AF was not related to the prevalence of significant CAD [10]. In our study chest pain type was not associated with the prevalence of significant CAD as well.…”
Section: Discussionsupporting
confidence: 84%
“…Similar to our results, a study by Guo et al . that focused on the elderly population (mean age 77.4 ± 6.3 years) showed that chest distress experienced by patients with AF was not related to the prevalence of significant CAD [10]. In our study chest pain type was not associated with the prevalence of significant CAD as well.…”
Section: Discussionsupporting
confidence: 43%